2012
DOI: 10.1053/j.seminoncol.2011.11.011
|View full text |Cite
|
Sign up to set email alerts
|

p53-Independent, Normal Stem Cell Sparing Epigenetic Differentiation Therapy for Myeloid and Other Malignancies

Abstract: Summary Cytotoxic chemotherapy for acute myeloid leukemia (AML) usually produces only temporary remissions, at the cost of significant toxicity and risk for death. One fundamental reason for treatment failure is that it is designed to activate apoptosis genes (eg., TP53) that may be unavailable because of mutation or deletion. Unlike deletion of apoptosis genes, genes that mediate cell cycle exit by differentiation are present in myelodysplastic syndrome (MDS) and AML cells but are epigenetically repressed: MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 143 publications
0
40
0
Order By: Relevance
“…Several groups have observed that terminal differentiation is induced in vitro when treating myeloid and other cancer cells with drugs or conditions that inhibit gene-silencing, chromatin-modifying enzymes (chromatin relaxation) (reviewed in ref. 13). These differentiation-mediated cell-cycle exits, like those that occur during normal tissue differentiation, do not require p53 and are readily induced in p53/p16-null cancer cells (10,(14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several groups have observed that terminal differentiation is induced in vitro when treating myeloid and other cancer cells with drugs or conditions that inhibit gene-silencing, chromatin-modifying enzymes (chromatin relaxation) (reviewed in ref. 13). These differentiation-mediated cell-cycle exits, like those that occur during normal tissue differentiation, do not require p53 and are readily induced in p53/p16-null cancer cells (10,(14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%
“…The reasons for this cell context-dependent response have been evaluated: differentiation is driven by relatively few master transcription factors (25). Myeloid cancer cells express master myeloid differentiation-driven transcription factors (e.g., CEBPA and PU.1) at high levels, yet the target genes of these transcription factors are epigenetically silenced (10,13,14,20,(26)(27)(28)(29) because of aberrant recruitment of silencing -instead of activating -chromatin-modifying enzymes to the transcription factors (20,27,30). Inhibition of silencing enzymes with drugs such as decitabine restores expression of numerous target genes of the transcription factors, including MYC antagonists (e.g., CEBPE and p27/ CDKN1B), that terminate proliferation (10, 14, 17, 20-22, 27, 30-32).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of the methylation pattern is achieved by DNMT1 function during DNA replication, whereas de novo methylation is primarily catalyzed by DNMT3a and DNMT3b (Pazienza et al, 2012). DNMT1 is a central component of the epigenetic network that mediates transcription repression (Saunthararajah et al, 2012). Overexpression of DNMT1 promotes global DNA hypermethylation (Biniszkiewicz et al, 2002).…”
Section: Lox-1 Mediates Hcy-induced Global Hypomethylationmentioning
confidence: 99%
“…The hypermethylation of CpG islands within promoter regions, and the resultant silencing of tumor-associated genes, are significant events involved in the pathogenesis of MDS (1). Previous studies have revealed that the DNA methyltransferase (DNMT) 1 and 3A enzymes contribute to aberrant methylation in MDS (2,3). Therefore, DNMTs have become potential targets for the treatment of MDS (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%